MODELING AND PREDICTION OF VOLUME AND AEREAL BIOMASS OF THE TREE VEGETATION IN A CERRADÃO AREA OF CENTRAL BRAZIL - Eder Pereira Miguel (Interciencia, 2017)
This research aims to adjust and select models to quantify the volume of the tree vegetation and its total and com - partmental biomass, in a ‘cerradão’ (forest savanna), in the municipality of Palmas, Tocantins, Brazil. A forestry inventory was performed in an area of 10.15ha, divided in sampling plots measuring 400m 2 , in which all living and dead standing trees ≥5cm DBH were sampled and identified, with a 20% error margin. The trees were cubed using the Smalian method and 84 of them were weighted. After obtaining the green mass by compartment, samples were removed in order to estimate the dry biomass. Mathematical models were adjusted to estimate total volume/biomass per unit area as well as by compartment. The Schumacher and Hall model was chosen. After processing, the inventory error was within the admissi - ble margin. Volume and total stoked biomass by hectare were 126 .71m³·ha -1 and 61.67Mg·ha -1 . For the bole and crown compartments the values were 79.23 and 47.17m³·ha -1 for volume and 29.70 and 31.98Mg·ha -1 for biomass. Dead trees summed 6.70% of the volume and 7.00% of the biomass, while leaves contributed with 7.3% of the total biomass. Bark summed 11.50% of the volume and 21.00% of the biomass. Volume and biomass stocks on the studied biome, when compared to oth - ers types of ‘cerradões’, are higher than those found on savannan formations.